With fentanyl lurking in street stimulant sales, CM vital. Issue 9 (24th February 2023) - Knopf, Alison
Abstract : Instead of going to various lengths to persuade or cajole or encourage patients addicted to stimulants to stop, the best method is still contingency management (CM), experts agree. In this modality, patients are paid to stop using, but the problem is that the payments are far too low (https://onlinelibrary.wiley.com/doi/10.1002/adaw.33437 ), and under federal anti‐kickback rules, the government still refuses to allow them to be higher. Richard A. Rawson, Ph.D., research professor at the Vermont Center on Behavior & Health at the University of Vermont, is the original developer, going back three decades, of this treatment. Now, with so many people thinking they are getting stimulants on the street, but instead consuming illicit fentanyl, Rawson says it's urgent that CM be used.